TEKTONIK AKTIF SESAR CIMANDIRI, KABUPATEN SUKABUMI, PROPINSI JAWA BARAT - SUPARTOYO
The research area is located along Cimandiri valley which covers from Pelabuhan Ratu Gulf to southern of Sukabumi regency city and Cimandiri fault located along this valley. The distribution of Cimandiri fault could be observed from morphology along Cimandiri valley, but the off set could not be seen from morphology. The knowledge about active tectonic can reveal about the potential of earthquake disaster which is possible to return again in the future as part earthquake mitigation effort. To analyze active tectonic of Cimandiri fault onducted along Cimandiri valley and based on ata of morphology, geological observation in the field, morphometry and seismicity, then these data will be integrated by each other for analyzing the active fault of Cimandiri. The data of landsat and SRTM, showed 3 trends of lineament along Cimandiri valley which are : N 85 degrees E-N 265 degrees E, N 55 degrees E-N 235 degrees E, and N 135 degrees E-N 315 degrees E. Based on field observation of morphology, showed 2 trends of lineament along Cimandiri valley, are : west-east on the western part of the research area and north east-south west on the eastern part. The lineament of triangular facet also showed on the western and eastern of research area. The result of field observation of geological structure showed subsidiary structure such as : slickenside, fault breccia, scarp, lithology off set, lineament, shear and gash fracture along Cimandiri valley. The measurement of slicken side is N 271 degrees E/ 55 degrees rake 15 degrees. The Cimandiri fault is a sinistral strike slip fault based on analyze of main force orientation (17 degrees N 31 degrees E), sinistral off set on sandstone which part from Cimandiri Formation at Cirajeg stream and modeling of fracture from Riedel (1929) and Skempton (1966). To analyze active tectonic of Cimandiri fault, the author used 5 parameters of morphometry these are : hypsometric curve, drainage basin asymmetry (AF), stream length- gradient index (SL), mountain front sinuosity (SE) mf) and ratio of valley floor width to valley height (Vf). Based on calculation and drawing of hypsometric curve, mostly along Cimandiri valley showing topography as young stadium and indicating as active tectonic. Calculation of AF showing that mostly of little drainage along Cimandiri valley, the value of AF is far from 50, it means that along Cimandiri valley has occurred tectonic tilting and indicating of active tectonic. Based on calculation of SL mostly on the research area the value of SL is more than 300 that indicates active tectonic. Calculation of Smf on the research area shows a range between 1,0454 to 1,9386 (less than 2) and indicates an active tectonic. The value of Vf in the research area has a range between 0,1856 to 21,6143. Value of Vf is less than 2 showing deep valley and indicate as active tectonic. Value of Vf more than 2 indicates that the erotional process than uplift. Therefore, based on morphometri calculation indicated that Cimandiri fault as an active fault. There were 7 sites of river terrace that found along Cimandiri valley is indicate that Cimandiri fault on the zone of active tectonic. Although earthquake epicenter was not found along Cimandiri Fault, field evidence in this thesis suggestion, this fault as an active fault system. Therefore, Cimandiri Fault should be classified and considerate as an active fault which has possibility to move again in the future.